Comprehensive insights into mechanism of nanotoxicity, assessment methods and regulatory challenges of nanomedicines - Ujwal Havelikar; Kabirdas B. Ghorpade; Amit Kumar; Akhilesh Patel; Manisha Singh; Nagma Banjare; Prem N. Gupta (Discover Nano, 2024)
Abstract Nanomedicine has the potential to transform healthcare by offering targeted therapies, precise diagnostics, and enhanced drug delivery systems. The National Institutes of Health has coined the term "nanomedicine" to describe the use of nanotechnology in biological system monitoring, control, diagnosis, and treatment. Nanomedicine continues to receive increasing interest for the rationalized delivery of therapeutics and pharmaceutical agents to achieve the required response while reducing its side effects. However, as nanotechnology continues to advance, concerns about its potential toxicological effects have also grown. This review explores the current state of nanomedicine, focusing on the types of nanoparticles used and their associated properties that contribute to nanotoxicity. It examines the mechanisms through which nanoparticles exert toxicity, encompassing various cellular and molecular interactions. Furthermore, it discusses the assessment methods employed to evaluate nanotoxicity, encompassing in-vitro and in-vivo models, as well as emerging techniques. The review also addresses the regulatory issues surrounding nanotoxicology, highlighting the challenges in developing standardized guidelines and ensuring the secure translation of nanomedicine into clinical settings. It also explores into the challenges and ethical issues associated with nanotoxicology, as understanding the safety profile of nanoparticles is essential for their effective translation into therapeutic applications.